How complex are intracellular immune receptor signaling complexes? - Bonardi, Vera; Dangl, Jeffery L. (Frontiers in Plant Science, 2012)
Nucleotide binding leucine-rich repeat proteins (NLRs) are the major class of intracellular immune receptors in plants. NLRs typically function to specifically recognize pathogen effectors and to initiate and control defense responses that severely limit pathogen growth in plants (termed effector triggered immunity, or ETI). Despite numerous reports supporting a central role in innate immunity, the molecular mechanisms driving NLR activation and downstream signaling remain largely elusive. Recent reports shed light on the pre- and post-activation dynamics of a few NLR-containing protein complexes. Recent technological advances in the use of proteomics may enable high-resolution definition of immune protein complexes and possible activation-relevant post-translational modifications of the components in these complexes. In this mini-review, we focus on research aimed at characterizing pre- and post-activation NLR protein complexes and the molecular events that follow activation. We discuss the use of new or improved technologies as tools to unveil the molecular mechanisms that define NLR-mediated pathogen recognition.